Mutu Biopelet dari Campuran Cangkang Buah Karet dan Bambu Ater (Gigantochloa atter) (The Quality of Biopellet from Rubber Seed Shell and Ater Bamboo (Gigantochloa atter)) - Prabawa, I Dewa Gede Putra; Miyono, Miyono (Kementerian Perindustrian, 2017)
Material characteristic showed that the rubber seed shell (RSS) has good potential to be used as the main material of biopellet with low ash content and high calorific value, while ater bamboo (Gigantochloa atter) has good potential to be used as biopellet additive because has high lignin content, so that it can be used as natural adhesive. The purposes of this research were to study the utilization of CBK and ater bamboo into biopellet and to analyze the quality of biopelet that has been produced. The compositions of CBK and ater bamboo were 100%:0%, 95%:5%, 90%:10%, 85%:15%, and 80%:20%. Pelletization process was done at pressure 597.24 kg/cm2, temperature 150oC, for 10 minutes. The best quality of biopellet was produced on the formulation of 85% CBK and 15% ater bamboo. It has 4.23% of moisture content; 0.84% of ash; 79.44% of volatile substances; 15.48% of fixed carbon; 4472.41 kal/g of calorific value; 8.30 mm of diameter; 32.66 mm of length; 1063.87 kg/m3 of bulk density; 91.93% of mechanical durability; 0.21% of nitrogen; 0.05% of sulphur; and chlorine content was less than 0.10 ppm. The best quality of biopellet has fulfilled the requirement of Indonesian Standards (SNI 8021: 2014), while based on European standards (EN 14961-2), biopelet had one parameter that didn’t fulfill the requirement, the mechanical durability (min. 96.5%).Keywords : Biopellet, alternative energy, rubber seed shell, ater bamboo (Gigantochloa atter)